Atendimento seguro ao paciente crítico de CTI livre de eventos adversos - PINHEIRO, Naiá Estrela (2019)
This study was the result of a study entitled: Patient care for CTI patients, free of adverse events, aimed mainly at monitoring the occurrence of adverse events in critically ill ICU patients attended at a University Hospital in Belém, State of Pará, Brazil. This is an exploratory retrospective study, with a quantitative approach. The data collection was performed using the trigger methodology developed by the Institute for Healthcare Improvement, with consultation of the medical records of patients admitted to the ICU on a monthly basis, following an average of 10 patients per month using the active search worksheet during the months of May to August 2018. The results were presented and discussed, corroborating with other authors of studies and researches in the area. The mean length of stay in the intensive care unit was 14.3 days, with patients predominantly male and> 60 years old. Most of the patients came from the surgical center. The mortality rate was 45% and the discharge taxax for improvement was 55%. Regarding the search for triggers, in the data collection, among the 40 patients, 38 triggers were found and 24 adverse events (AE) were confirmed in 25 patients. The AEs found were: pneumonia associated with mechanical ventilation, primary infection of the bloodstream, pressure injury and skin infection. It was observed the great importance in the search for new methodologies to reduce the incidence of adverse events in hospital environments, to encourage notifications and to create a culture of patient safety that permeates among managers, health professionals and users.